Dampak Pembelajaran Online Pada Motivasi Belajar Siswa Sekolah Dasar - Salamah, Evi Rizqi; Rifayanti, Zuni Eka Tiyas (Universitas Nusantara PGRI Kediri, 2022)
The aims of this study were (1) to describe the impact of online learning on the learning motivation of fifth graders at SDN Wonoplintahan II Sidoarjo, (2) to describe the learning process of fifth graders at SDN Wonoplintahan II Sidoarjo, (3) to describe the learning motivation of fifth graders. at SDN Wonoplintahan II Sidoarjo, (4) to describe the obstacles during the learning process at SDN Wonoplintahan II Sidoarjo. The method used in this research is descriptive using a qualitative approach. Sources of data and research data came from fifth grade teachers and fifth grade students at SDN Wonoplintahan II Sidoarjo. The data collection technique used is interview. The results showed that the learning process used was online learning via Zoom, Google Classroom and Whatsaap were less able to motivate student learning because they did not understand the material presented by the teacher. In addition, there is also a lack of assistance when they study.